A Comprehensive and In-depth Bibliometric Analysis of Human Resource Management Practices in Small and Medium Sizes: Trends, Influences, and Future Directions - Ellafi, Ayad; Al-Mekhlafi , Al-Baraa Abdulrahman; AL-Tahitah, Ali Nasser; Alghamati, Adel K. (International Review of Management and Marketing, 2025)
This study seeks to develop a roadmap for (Human Resource Management (HRM) in Small and Medium Size (SMEs)) using bibliometric analysis techniques. It also seeks to examine elements have affected HRM in last two decades. The study examined 612 of 825 documents from Scopus database. Bibliometric analysis comprises three primary techniques such as performance analysis, science mapping, and network analysis. We utilize VOSviewer software to examine authorship, co-occurrence, co-citations, and thematic mapping. Based on results obtained, 2023 is most productive year with 104 publications. Surya, Batara has got the most influential author based on total citation, and University of Lincoln, UK, is most prominent organization. Additionally, USA is most influential country. "Sustainability (Switzerland)" is most influential journal in its category. Furthermore, top cited article, A structured review of Lean Six Sigma in various industrial sectors. This study has found five themes’ clusters of “human resource management practices in small and medium sized enterprises”.